“The lost world”: Tuvan culture in the center-periphery model of the geocultural and sociocultural space - Popkov, Yuri V.; Tyugashev, Evgeny A. (The New Research of Tuva, 2022)
The article looks at the Tuvan culture on the basis of the centre/periphery model in theoretical thought, also making use of the subject-oriented approach in analyzing the dialogue of culture. Focusing on Tuvan culture as a multi-aspect entity, the article studies its representations within the centre/periphery view. The uniqueness of Tuvan culture is largely due to a special geographical location it occupies on the Asian continent. For a relatively long period, it was at the same time a periphery for many powerful states and empires, and lay at the very heart of Asia. Tuva was hard to reach and geographically isolated by natural barriers. The cultural mediation of this geographical factor gives way to an inversive effect of building the “centre” of Tuvan culture, as well as the dynamic balance between the “centre” and “periphery” statuses in the course of history. The article concludes that in the space of theoretical model of the “centre” vs. “periphery” Tuvan culture acts ambivalently. It can be best described through the metaphor of the cultural palimpsest as a kind of a buildup of elements originating from a variety of cultural complexes.